Evaluation of efficiency of Harpin protein in inducing SOD enzyme as one of defense reaction at Wheat. (Damascus University Journal of agriculture sciences, 2025)
We applied in our study, Recombinant Harpin protein ,which produced locally in Syria,on 10-day wheat seedlings by spraying, to study its effect in increasing wheat resistance by measuring the activity of superoxide dismutase (SOD) enzyme, sterilized distilled water was used as a control, samples collected from plants at (0, 1, 2, 4, 18, 24, 48, 72, 96) hour post-treatment and stored at -70°C, total protein was extracted from frozen samples ,their concentrations were derermined by Bradford assay.
Keywords: Wheat; Harpin protein; SOD enzyme; Syria